Metaverse in Tourism and Hospitality: Empirical Evidence on Generation Z from Italy - Elisa Rancati; Alessandro d’Agata (European Scientific Journal, ESJ, 2022)
The paper intends to analyze the change taking place in tourism marketing due to the metaverse. The tastes and needs of today's new generations of tourists, especially Generation Z, are becoming more and more in line with new technologies. Tourism marketing requires a change in the way of promoting and telling a product and a brand. The objective of the paper will be to analyze the digital tools of the Metaverse and of the “immersive” technologies. The results of a survey that investigates people's propensity to use digital tools and new technologies will also be presented. Further objectives will be to understand the role these technologies will have in the world of travel and to provide a “guide” for tourism-related businesses, trying to help them face and understand a highly dynamic sector.